Properties of oil palm shell lightweight aggregate concrete containing fly ash as partial sand replacement - Muhammad Nazrin Akmal, Ahmad Zawawi (2018)
The steady growth of the palm oil industry has led to the generation of the palm oil mill by-product known as oil palm shell (OPS) amounting more than 4 million tonnes annually which are dumped in the landfill. At the same time, the annual world production of fly ash (FA) which is a by-product of coal-fired electric power plants is approximately 350 million tonnes. Due to large production, these waste are also dumped that in turn, significantly affects the surrounding environment. On the other hand, the growing construction industry has led towards the increase in river sand mining activities. However, unregulated mining by the authorities may pose adverse impact towards the environment as it lowers the stream bottom, which in turn may lead to bank erosion. The growing demand for construction material and environmental issues created from the by-products of palm oil industry as well as coal industry have initiated research towards producing a new lightweight concrete. OPS has been previously utilized with POFA and FA as partial cement replacement. However, it is non-trivial to mention that study on the integration of fly ash (FA) as sand replacement in OPS LWAC has yet been reported. Thus, this research focuses on investigating the properties of Oil Palm Shell Lightweight Aggregate Concrete (OPS LWAC) containing various percentage of FA as partial sand replacement. Fly Ash (FA) is utilized as partial sand replacement in the production of Lightweight Aggregate Concrete (LWAC) in order to reduce sand usage in construction, reduce pollutions as well as the amount of waste disposed. Meanwhile, the use of OPS in lightweight aggregate concrete (LWAC) as a coarse aggregate replacement will help to preserve natural resources such as granite and limestone. The plain OPS LWAC content with 100% sand was used as a control mix. Then, a series of OPS LWAC mixes with FA of various percentages such as 10%, 20%, 30% and 40% were prepared. The OPS was utilized as coarse aggregate with 100% replacement throughout the research. The best mix acquired from the trial mixes were used to investigate the mechanical and durability properties of OPS LWAC. The effect of curing namely water curing, air curing and initial water curing regimes on mechanical properties aspect of OPS LWAC containing FA has been determined. Furthermore, other durability properties tests have been carried out namely sulphate resistance test, water absorption and carbonation. All specimens were tested until 9 months. OPS LWAC containing 10% FA performs the best amongst all percentages in terms of mechanical and durability properties. The inclusion of a suitable amount of fly ash produces larger amount of C-S-H gel from both hydration and pozzolanic reaction which fills in the void of concrete internal structure making the concrete denser and stronger. It was demonstrated that 40% of FA replacement provided the worse effect to the OPS LWAC in term of mechanical and durability properties. The findings show that water curing is the best curing method to ensure better performance on compressive strength, flexural strength, modulus of elasticity and splitting tensile strength of OPS LWAC containing FA followed by initial water curing and air curing. Also, OPS LWAC with 10% FA exhibit higher durability compared to control specimens and others mixes when subjected to sulphate attack. OPS LWAC with 10% FA has better performance in sulphate solutions since the pozzolanic reactions reduce the quantity of calcium hydroxide which is vulnerable towards aggressive environment. No carbonation rate was detected for specimens subjected to water curing and initial water curing except for air curing. Water curing promotes better hydration process and pozzolanic reaction that improves the internal structure of OPS LWAC containing FA causing it to exhibit lower absorption value compared to other curing methods.